Integration of a heating and cooling system driven by solar thermal energy and biomass for a greenhouse in Mediterranean climates. (25th February 2023) - Prieto, J.; Ajnannadhif, R.M.; Fernández-del Olmo, P.; Coronas, A.
Highlights: A thermal model for a greenhouse is developed and validated on TRNSYS. A system with solar collectors, biomass boiler and absorption chiller is proposed. The proposed system and the greenhouse for a tomato crop are simulated in Almeria. The system operation is studied at winter and summer conditions. Heating and cooling demand and the seasonal performance of the system is obtained. Abstract: World population growth, climate change, and water scarcity will increase food vulnerability, especially in developed countries. Therefore, increasing crop productivity is one of the main challenges to be addressed in the next years. In this sense, intensive horticulture will play a key role to supply the growing demand for food. In greenhouse farming in Mediterranean climates the passive control of the greenhouse ambient conditions is insufficient and, therefore, the use of active heating/cooling systems is required. The status of solar thermal, biomass, and absorption heat pump technologies makes the active management of greenhouse climate conditions technically feasible. At the same time, the utilization of solar thermal and biomass energies allows reducing, as much as possible, the consumption of natural resources and the generation of waste. In this study, we present a system based on solar thermal energy, biomass, and an air-cooled absorption chiller that are integrated to control the temperature of a greenhouse for tomato production in Mediterranean climates. The greenhouse thermal demand is firstly modelled with the TRNBuild tool and validated with real data obtained from a monitored greenhouse in southern Spain. The validated model is used to both study the system operation and determines the annual heating and cooling demands of a greenhouse with tomato crop (26.31 kW·h·m −2, and 61.97 kW·h·m −2, respectively), the energy performance of the system (solar fraction 54.92 %, and absorption chiller seasonal COP 0.624), and the annual biomass operational cost (2.70 €·m −2 ). This study also provides the specification of the main components (absorption chiller capacity, solar collector technology, absorbance area, biomass boiler thermal capacity, and water tank volume…) that can achieve these results. Moreover, the control for different typical days is shown.